2016
DOI: 10.1080/08952841.2015.1138047
|View full text |Cite
|
Sign up to set email alerts
|

The experience of high-frequency gambling behavior of older adult females in the United Kingdom: An interpretative phenomenological analysis

Abstract: The prevalence of older adult female gambling participation and gambling disorder is increasing in the UK, and there is a paucity of published research available to understand possible risk factors for frequent gambling in this demographic. The aim of the current study was to identify and explore motivations and patterns of gambling behavior in high-frequency older adult female gamblers in the UK, from the perspective of the individual and in the context of their experience of aging. Ten UK older adult female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…Positive perceptions about the social and financial benefits of gambling may also impact on how some sub-groups of women may conceptualise and experience gambling-related harm and may be a key risk factor for problem gambling [37, 68, 69]. For example, Thomas and Lewis [37] found older women had lower perceptions of the harm associated with gambling at EGM venues because they felt that there was a trade-off between the social benefits of the gambling environment and the money they lost on EGMs [37].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Positive perceptions about the social and financial benefits of gambling may also impact on how some sub-groups of women may conceptualise and experience gambling-related harm and may be a key risk factor for problem gambling [37, 68, 69]. For example, Thomas and Lewis [37] found older women had lower perceptions of the harm associated with gambling at EGM venues because they felt that there was a trade-off between the social benefits of the gambling environment and the money they lost on EGMs [37].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Thomas and Lewis [37] found older women had lower perceptions of the harm associated with gambling at EGM venues because they felt that there was a trade-off between the social benefits of the gambling environment and the money they lost on EGMs [37]. Similarly, research has demonstrated that older women felt safe and welcomed in gambling environments, reporting that the benefits of attending gambling venues heavily outweighed monetary losses from EGMs [68]. While they described regularly gambling more money on EGMs than they intended to, they perceived gambling as one of the few available and accessible leisure activities for older women [68].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, and perhaps less well understood, are differences between subgroups of women. For example, studies suggest that older women may be particularly vulnerable to gambling harm because of their increased social isolation, loneliness, lack of leisure alternatives, and physical health problems [ 34 , 35 ]. Studies suggest that women’s gambling behaviour may increase as women get older as a way to occupy their time after retirement, and after their children leave home [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Deterioration of physical health in old age is related to depression ( Aylaz et al., 2012 ). More specifically, recent qualitative research has indicated that when older adult problem gamblers experienced negative outcomes in relation to transitioning into older adulthood such as depression, they often engage in avoidant rather than adaptive coping behavior ( Pattinson & Parke, 2016 , 2017 ). These participants stated that they felt that their physical decline was inevitable, and that the negative outcomes would continue, because they did not have the resources to address the problems and to improve their social and physical circumstances ( Pattinson & Parke, 2017 ).…”
Section: Introductionmentioning
confidence: 99%